STRAIN ESTIMATION FROM FLATTENED PARALLEL FOLDS: APPLICATION OF THE WELLMAN METHOD AND MOHR CIRCLE - Shah J.; Srivastava D.C. (My University, 2006)
Parallel folds exhibit a characteristic orthogonal relationship between the tangent and the corresponding isogon drawn at any point on folded surface. Modification of parallel fold to flattened parallel fold by superimposition of homogeneous strain introduces an angular shear along the tangents at different points. The angular shears in different directions, obtained by measuring angles between the tangents and the corresponding isogons, can be used for estimation of flattening strain by a variety of geometrical and numerical methods. We show that several simple geometrical techniques, such as the Wellman method and the Mohr circle method, can rapidly decipher the strain from flattened parallel folds. These methods, in contrast to most of the existing methods of strain estimation, are independent of the assumption that one of the principal strain directions parallels the axial trace on the profile plane of fold.
Keywords: FLATTENED PARALLEL FOLD; OBLIQUE FLATTENING; ANGULAR SHEAR; WELLMAN METHOD; MOHR CIRCLE